Regulatory effects of sterols and bile acids on hepatic 3-hydroxy-3-methylglutaryl CoA reductase and cholesterol 7α-hydroxylase in the rat - S. Shefer (Journal of Lipid Research, 1973)
Specific activities of the hepatic microsomal enzymes 3-hydroxy-3-methylglutaryl CoA (HMG CoA) reductase and cholesterol 7α-hydroxylase were studied in rats fed sterols and bile acids. The administration of bile acids (taurocholate, taurodeoxycholate, taurochenodeoxycholate) at a level of 1% of the diet for 1 wk reduced the activity of HMG CoA reductase. Taurocholate and taurodeoxycholate, but not taurochenodeoxycholate, inhibited cholesterol 7α-hydroxylase. Dietary sitosterol produced increases in the specific activity of HMG CoA reductase (3.6-fold) and cholesterol 7α-hydroxylase (1.4-fold), and biliary cholesterol concentrations in this group more than doubled. Compared with controls fed the stock diet, the simultaneous administration of sitosterol and taurochenodeoxycholate resulted in a 60% decrease of HMG CoA reductase activity and no change in cholesterol 7α-hydroxylase activity or biliary cholesterol concentration. Rats fed sitosterol plus taurocholate had nearly normal HMG CoA reductase activity, but cholesterol 7α-hydroxylase was inhibited and biliary cholesterol remained high. Bile acid secretion rates and biliary bile acid composition were similar in controls and sterol-fed animals. In all groups receiving bile acids, biliary secretion of bile acids was nearly doubled and bile acid composition was shifted in the direction of the administered bile acid. It is concluded that the composition of the bile acid pool influences the hepatic concentrations of the rate-controlling enzymes of bile acid synthesis.